Concordance between macroinvertebrate communities and the typological classification of white and clear-water streams in Western Brazilian Amazonia - Roque, Fabio de Oliveira; Lima, Diego Viana Melo; Siqueira, Tadeu [UNESP]; Vieira, Lisandro Juno Soares; Stefanes, Maurício; Trivinho-Strixino, Susana (Instituto Virtual da Biodiversidade, 2012)
Neste trabalho, nós investigamos se há correspondência entre comunidade de macroinvertebrados e classificação de igarapés em águas claras e brancas no oeste da Amazônia. Nós trabalhos em duas bacias hidrográficas, Rio Moa (águas claras) e Rio Azul (águas brancas) no Parque Nacional da Serra do Divisor, Acre, Brasil, amostrando 10 igarapés em cada bacia. Coletamos 2952 indivíduos, distribuídos em 134 taxa. Nossos resultados mostram que a comunidade de macroinvertebrados, identificada com baixa e alta resolução taxonômica, responde claramente a classificação tipológica de igarapés em águas claras e brancas.A principal implicação dos nossos resultados no âmbito de biomonitoramento é que a partição da variação biótica entre igarapés de águas claras e brancas pode melhorar a racionalidade e implantação de sistemas de avaliação ambiental na Amazônia.

In this study we have attempted to answer whether there is correspondence between aquatic macroinvertebrate communities and the typological classification of white and clean-water streams in western Amazonia lowlands. We worked within two distinct hydrographic basins: Moa River catchment (clear-water streams) and Azul River catchment (white-water streams) in Serra do Divisor National Park, Acre State, Brazil, sampling 10 streams in each basin. A total of 2,952 individuals were collected, distributed among 134 taxa. Our results show that macroinvertebrate communities, at genus as well as family level, are in concordance to a priori classifications that distinguish between white and clear water streams. The main implication of our results for biomonitoring is that biotic variation between white and clear streams can be partitioned regionally, which would improve the bioassessment accuracy of the Amazonian streams.
Concordância entre comunidade de macroinvertebrados e classificação tipológica de igarapés em águas brancas e claras no oeste Amazônico, Brasil
Keywords: insetos aquáticos; biodiversidade; região neotropical; biomonitoramento; Brasil; aquatic insects; biodiversity; neotropical region; biomonitoring; Brazil